The Urgency of Electronically Storing Notary Protocol Archives Documents in the Concept of Progressive Law in Indonesia - Dana Ayu Fitrianingrum; Tunggul Anshari Setia Negara; Diah Aju Wisnuwardhani (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
The development of information technology has encouraged transformation in the practice of notarial administration, including the urgency of digitizing notary protocol storage. This research aims to analyze the legal needs of the e-documents storage system in a progressive legal perspective, emphasizing the regulatory vacuum and the urgency of norm reconstruction. Using a normative juridical approach and qualitative analysis of legal documents as well as the results of previous studies, it is found that the absence of explicit regulation in the Notary Office Law regarding digital archives creates legal uncertainty and evidentiary risks. This study argues that electronic-based storage of notarial protocols should be recognized as a normative necessity in line with the principles of expediency and legal certainty. The conclusion of this study confirms the importance of new regulations that provide legitimacy to notary e-documents as part of the state's responsibility in realizing efficient, fair, and accountable legal services.